Oral conditions and body weight in children from a public school in Manaus, AM, Brazil - Samara Pinho ASSI; Juliana Rico PIRES; Ana Emília Farias PONTES; Eliane Marçon BARROSO; Elizangela Partata ZUZA
Abstract Introduction Some studies have pointed to links between the prevalence of caries and periodontal disease, and the occurrence of overweight or obesity; but, few studies have been conducted in children. Objective To assess the relationship between periodontal disease, tooth decay and body weight in children from a public school in Manaus, AM, Brazil. Material and method The study included one hundred and sixty-nine children. Records were obtained of decayed, missing and filled (DMFT) permanent teeth, and of decayed, extracted, or filled (DEF) deciduous teeth, as well as the record of the community periodontal index (CPI). The classification of body weight category was obtained in percentile using the z-Score table. Result Higher averages of weight and body mass index (BMI) were seen in the overweight and obesity groups (p<0.05). All groups were similar regarding the DMFT /DEF and CPI codes from 0 to 4 (p>0.05). All groups showed higher averages of CPI 0 in comparison with other CPI codes from 1 to 4 (p<0.05), and most of the children showed sites with probing depth <3.5 mm and without bleeding on probing. Conclusion There was no relationship between body weight and the occurrence of dental caries and periodontal disease in the studied population. Obesity and overweight showed no negative influence on the increase in the prevalence of these diseases.